Eﬃciency of ﬂoating ﬂoors on CLT or concrete plate in the low frequency region - Hermansson, Anton (My University, 2018)
In order to fulﬁl requirements regarding impact sound insulation between two ver-tically adjacent rooms, a ﬂoating ﬂoor construction is a commonly used technique. However the understanding of the acoustical performance of the ﬂoor construction at low frequencies is limited. This thesis aims to evaluate which physical parame-ters in the diﬀerent layers of a ﬂoating ﬂoor construction that are important for the improvement of impact sound insulation below 200 Hz. Two diﬀerent kinds of base ﬂoors are tested, concrete and cross laminated timber, CLT. The impact sound insulation improvement is evaluated using a numerical model developed in the ﬁnite element software COMSOL Multiphysics for extraction of vibration levels below the ﬂoor. The ﬂoor is considered being placed in an inﬁnite baﬄe and the sound radiation is calculated using the Rayleigh integral. Applying a ﬂoating ﬂoor to a structural plate of either concrete or CLT changes the radiated sound power from the ﬂoor in diﬀerent ways. Below the mass-spring-mass resonance frequency created by the three layers, the eﬃciency of the ﬂoating ﬂoor is mainly controlled by how the modal content of the ﬂoor is changed, both in frequency and amplitude. Above the resonance the eﬃciency of the ﬂoating ﬂoor follows expected theoretical improvements to diﬀerent extent. The most important physical parameters in a ﬂoating ﬂoor construction are accord-ing to this study the stiﬀness of the interlayer as well as the density and thickness of the ﬂoating ﬂoor slab. The study shows that the density of the interlayer as well as the damping of the ﬂoating slab is less important for the eﬃciency of the ﬂoating ﬂoor. When increasing the thickness or the density of the ﬂoating ﬂoor slab, the sound insulation improvement at the lowest frequencies (f < 30 Hz) is better for the CLT plate, attenuating the radiated sound power to almost the same amplitudes as for the corresponding concrete case. Above the ﬂoating ﬂoor resonance the slope of the sound insulation improvement is in general steeper for the concrete cases. However no other general tendency can be seen when studying the diﬀerence between applying the same ﬂoating ﬂoor construction to the diﬀerent structural plates.
Keywords: Akustik; Building Futures; Acoustics; Building Futures